PHRASAL VERBS AND THEIR CHARACTERISTICS ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2023)
This article examines the fascinating field of Phrasal verbs and how they are an essential and often challenging aspect of learning English. They are combinations of a verb and one or more particles (usually prepositions or adverbs) that create a new meaning. Phrasal verbs can be inseparable, separable, or transitive, presenting unique characteristics that learners must understand to use them effectively